The Legal Gap in the Regulation of Hospital Responsibility in Health Service Force Majeure Cases (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
In the healthcare system, hospitals have a legal responsibility to ensure the safety and rights of patients while receiving medical services. However, in certain emergency situations that are unpredictable—such as natural disasters, epidemics, social unrest, or technical disruptions beyond human control—hospitals face challenges in fulfilling their responsibilities optimally. These situations are often categorized as force majeure or circumstances of necessity. Issues arise when there is no clear and definite legal regulation regarding the extent to which hospitals can be exempted from legal responsibility in force majeure situations. This creates a legal gap that could harm both the hospital and the patients. This research aims to examine and analyze the legal gap regarding hospital responsibility in force majeure situations and provide a conceptual overview of the direction for forming ideal legal norms in the future. This research uses a normative juridical method, with a legislative and conceptual approach. The data sources consist of primary legal materials such as laws, government regulations, and technical regulations in the healthcare field; secondary legal materials such as literature, journals, and legal articles; and tertiary legal materials such as legal dictionaries. The analytical technique used is descriptive-analytical, focusing on the systematic interpretation of existing legal norms and theoretical approaches to the concepts of legal responsibility and force majeure in healthcare services. This research is expected to contribute academically and provide a foundation for the formulation of responsive and just legal policies in dealing with extraordinary situations in the healthcare sector. By addressing this legal gap, the study aims to provide a basis for future legal reforms that will protect both healthcare providers and patients in the face of unforeseen circumstances that may affect the provision of healthcare services.